Modifikasi Sistem Transmisi pada Mesin Pencacah Sampah/Limbah Plastik dengan Sistem Crusher dan Silinder Pemotong Tipe Reel - Junaidi - -; Ichlas Nur -; Zulfikar - -; Nasirwan - - (Jurnal Ilmiah Poli Rekayasa, 2016)
An increasing number of plastic waste, but can be recycled into other products in the form of granules before further processing into a grain pellets and injection molding processes to produce products such as buckets, plates, bottles and others. To be processed into the required form of granules of plastic thrasher. Even so small plastic recycling industry is still constrained within a plastic enumeration process because the machine used his ability was not maximal.The purpose of this study is a modification of the transmission system thrasher plastic crusher system and cylinder-type cutter reel and technical evaluation. This study was conducted over two years, the first year the design and manufacture of machinery, the second year is the technical evaluation of the engine, improved engine performance. From the results of the study year I found some weaknesses machines namely, 1) the machine is often hampered by the transmission belt on the motor shaft with shaft reducer as drive unit crusher often slip when a large load, 2) transmission gears hipoid of the motor shaft with shaft type unit reel get a great friction and cause the sound very noisy. To improve the performance of the engine of the transmission system needs to be fixed.From the results of the design redesign the engine in the second year, namely, the installation of a connector axle of the motor shaft with shaft-type knife reel player. Axle used is commonly used in car axle Carry. Likewise, the transmission system between the motor shaft to the reducer as a successor to the rotation axis of the blade type crusher players use the chain sprocket to avoid slip on a rotating shaft. The results of performance testing crusher machine on lap 75 RPM and cylinder-type reel cutters 1450 RPM, engine capacity ± 130 kg / h on the cylinder type crusher and the reel-type cylinder engine capacity of ± 165 kg / h at an aperture sieve Ø 1,5 cm, with uniformity of grain 85%.